EVALUASI PELAKSANAAN JAM OPERASIONAL HIBURAN UMUM DI KOTA PEKANBARU ( EVALUASI PERATURAN DAERAH NOMOR 3 TAHUN 2002 TENTANG HIBURAN UMUM) - Restu D Butar-Butar; Ernawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Until now the problem of public entertainment that violates the operationalhours of public entertainment in Pekanbaru still can not be solved well, so manypublic entertainments that violate predefined operational hours. From that issue,it is necessary to evaluate the implementation the operational hours of publicentertainment in Pekanbaru. The purpose of this research is to evaluate theRegional Regulation No. 3 of 2002 on Public Entertainment particular theimplementation of the operational hours of entertainment and determine anyfactors that hinder evaluation of Pekanbaru Regional Regulation No. 3 of 2002on public entertainment in particular exercising their operational hours ofentertainmentIn this research, researcher used N Dunn Wiliiam theory that explains thereare six evaluation criterias, namely effectiveness, efficiency, adequacy, equity,responsiveness and accuracy. This research uses qualitative descriptive methodand technique of data collection was done by interview, observation andliterature study.Based on result of interview, researcher noted that Pekanbaru RegionalRegulation No. 3 of 2002 on Public Entertainment has not correspondedanymore to the situation which already great development in Pekanbaru. Theregulation has been ineffective. It was seen from the goals and objectives are notperfect, because inefficient in terms of time and effort are still lacking, it is notenough to satisfy the needs of society, in distributing benefits to the group policyis still not evenly distributed, there is still a lack of responsiveness to theproblems that employers facing public entertainment and public entertainmentfor many entrepreneurs and there are many cons to this rule. This rule is nolonger appropriate very much between expectation and reality. This regulationmust be revised again to strengthen the legal basis in the implementation of theoperational hours of public entertainment. The factors that hinder theimplementation of the evaluation for operational hours of public entertainmentin this regulation number 3 of 2002 on public entertainment are psychologyfactors, economic factors, technical factors and political factors.Keywords: Evaluation, Policy, Regional Regulation